2015
DOI: 10.1159/000368510
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-Alpha and 8-Hydroxy-2'-Deoxyguanosine are Associated with Elevated Urinary Angiopoietin-2 Level in Type 2 Diabetic Patients with Albuminuria

Abstract: Background/Aims: We previously showed that urine and serum Angiopoietin-2 (Ang-2) levels increased significantly with the degree of albuminuria in diabetes patients, but the reasons remain unclear. Consequently we aimed to determine whether there was an association between Ang-2, inflammatory cytokines (TNF-α and IL-18) and reactive oxygen species (8-OHdG and SOD) in type 2 diabetes patients with albuminuria. Methods: This retrospective study evaluated 113 patients with type 2 diabetes and normoalbuminuria, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…In type 2 diabetic patients, serum and urine TNF-α level increased significantly with the degree of albuminuria [15]. In rats with renal failure, TNF-α naturalization prevented albuminuria, reduced fibrosis, decreased macrophage infiltration [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…In type 2 diabetic patients, serum and urine TNF-α level increased significantly with the degree of albuminuria [15]. In rats with renal failure, TNF-α naturalization prevented albuminuria, reduced fibrosis, decreased macrophage infiltration [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Ang2 overexpression-induced albuminuria and glomerular endothelial apoptosis were found to be consistent with the upregulation of VEGF-A signaling and nephrin phosphorylation in diabetic disease [44,[57][58][59]. A recent study demonstrated that upregulation of Ang2 in the urinary was associated with TNF-a and 8-hydroxy-2 0 -deoxyguanosine (8-OHdG, a type of reactive oxygen species) in type 2 diabetic patients with albuminuria, but the mechanism was unclear [61]. A recent study demonstrated that upregulation of Ang2 in the urinary was associated with TNF-a and 8-hydroxy-2 0 -deoxyguanosine (8-OHdG, a type of reactive oxygen species) in type 2 diabetic patients with albuminuria, but the mechanism was unclear [61].…”
Section: Diabetic Nephropathymentioning
confidence: 87%
“…Increased levels of Ang2 are associated with worsening of renal structure, and Ang2 is elevated in the serum and urine of diabetic patients [76,77]. Furthermore, TNFα and ROS are associated with elevated urinary Ang2 levels in albuminuric T2DM patients [78]. Glomerular lesions, mesangial expansion, podocyte lesions and a disturbed Ang2/Ang1 balance in the cortex of the kidney were found in a pig model of diabetes [79].…”
Section: Diabetic Nephropathymentioning
confidence: 98%